Analisis Penyakit Tanaman Bawang Merah Menggunakan Metode Teorema Bayes - Fadhil Muhamad Basysyar; Ade Rizky Rinaldi (STMIK IKMI Cirebon, 2020)
Shallot plants or in Latin Alliumascalonicum L is a horticultural plant that gets a lot of attention from both the public and the government. Over the past few years shallots are included in the top six vegetable commodities that are exported together with cabbage, cabbage or flower cabbage, chili, tomatoes, potatoes. Onion plants are very susceptible to disease that can strike at any time. Some diseases that can attack the onion plant include Onion Caterpillar Disease, Leaf Snorer Disease, Trip, Moler Disease, Trotol, Dew Feather and Anthracnose. In this study using the Bayes theorem expert system, each symptom has a density value to the disease which is then calculated using the formula of the Bayes Theorem Method and processed using certain rules and inference using Forword Chaining. This research is expected to help the onion farmers in diagnosing the disease so that it can reduce the material losses with less than 60%.